A Systematic Review of Exercise Intervention Program for People With Substance Use Disorder - Zhang, Zhilei; Liu, Xiujuan (Frontiers in Psychiatry, 2022)
Addiction has been attributed to development of habit-based neural circuits that promote continued substance use despite a conscious wish to abstain. The goal of this study was to determine if physical exercise could serve as an alternative habit to replace habitual substance use, and whether this exercise intervention methods differed for opioid vs. amphetamine Dependents. A total of 14 randomized controlled experimental literatures on exercise intervention in people with opioid and amphetamine use disorder were screened,the 14 literature included 4 opioids and 10 amphetamines.From the 14 literature, the information of intervention program elements were counted respectively.Independent sample t-test was used to compare the similarities and differences between the two intervention methods, and intervention mechanism of dependents were discussed. All rehabilitation exercises for opioid dependents use aerobic exercise, while most rehabilitation exercises for amphetamine dependents use aerobic exercise, and a few use aerobic and anaerobic mixed exercise. There is no significant difference in exercise time, exercise frequency and cycle between the two intervention schemes (P>0.05). The rehabilitation indicators of opioid and amphetamine dependents generally include psychological indicators and physiological indicators, and most of the tests mainly focus on measuring psychological indicators such as mood and drug craving of dependents.The goal of exercise intervention for opioid and amphetamine dependents is similar, the first is to improve mood, reduce craving, improve sleep, and the second is to enhance physical fitness. In the treatment of Substance use disorder , exercise intervention can be used as an auxiliary treatment. Exercise intervention emphasizes low intensity and high frequency. Exercise intervention tends to cultivate long-term exercise habits or exercise lifestyle. Based on this "habit" mechanism, exercise can complete the substitution of material dependence.